(untitled) (PAMPA, 2025)
This article aims to discuss the spatial distribution of the economy of Northeastern Brazil within its city networks. Based on the urban hierarchy defined in the Regions of Influence of Cities research, the classification of municipalities and the division of the areas influenced by the three northeastern metropolises – Fortaleza, Recife and Salvador – were used as the framework for analysis. The Gross Domestic Product (GDP) data of the Municipalities for the period 2002-2020 were analyzed descriptively. The scope of the regional growth of Services was assessed, showing influence from the growth pattern via social inclusion and mass consumption, a phenomenon that occurred at the beginning of the 21st century. Thus, the socioeconomic performance of the region is related to the expansion of consumption, limited by the capacity of the tertiary sector to meet the needs of the population and absorb its labor force, given the limits of this growth model.